Persepsi Masyarakat tentang Haramnya Investasi di Pasar Modal Syariah - Hidayah, Noor Laili; Aslicha, Ghina; Hana, Kharis Fadlullah (Sharia Faculty Islamic Economic Law Study Department, 2020)
Public knowledge must also be comprehensive with the times. People are already familiar with the word